A novel SCN5A variant causing Brugada syndrome: a case of Slovenian family - Karin Writzl; Tadej Žlahtič; Maruša Debeljak; Mirko Topalović; Martin Rauber; Bor Antolič; Anja Zupan Mežnar; Luka Klemen; Andrej Pernat; David Žižek; Matjaž Šinkovec (Zdravniški Vestnik)
Brugada syndrome is an inherited cardiac channelopathy with pathognomonic early repolarization alteration (Brugada sign) and is associated with a high risk for sudden death from ventricular fibrillation (VF). Documented ventricular arrhythmic events, sudden unexpected death in family members, accurate evaluation of Brugada signs and arrhythmic syncope, and genotyping of SCN5A for cardiac fast sodium channel Nav1.5, are the most important steps in diagnostic and prognostic evaluation. Treatment with quinidine and the recently introduced catheter ablation procedure are important methods for reducing the high burden of ventricular arrhythmias. However, the decision of whether to implant a cardioverter defibrillator to prevent sudden cardiac death is essential. We present a case of a patient and his family with a novel heterozygotic variant in exon 15 of the gene SCN5A(NM_000335.5):c.2271del, p.(Ile759PhefsTer6), associated with cardiac arrest because of VF during intensive physical effort, with mild structural heart disease, and a short QT. We discuss current guidelines for optimal management of patients with suspected Brugada syndrome.